Gerakan Islah Muhammad Rashid Rida dan pengaruhnya terhadap kebangkitan Islam di Malaysia - Farid Mat Zain, (Penerbit Universiti Kebangsaan Malaysia, 2007)
This article discusses the personality of an Egyptian Islamic reformist, Muhammad Rashid Rida and his contributions to Islamic reformism and revivalism in Malaysia. It presents his activities and efforts to strengthen Muslim community that was under the Western occupation and rule then. These activities seem to have led to the awakening of the Muslims in Egypt and elsewhere in the Muslim world including Malaya and then Malaysia. The article also analyses how Muhammad Rashid Rida had spread and contributed to Islamic revivalism in Malaysia. Several aspects of his contributions are identified such as his methods of Islamic missionary activities and Islamic education to strengthen the Muslim community. To explore the influence of the Muslim thinker, this article draws upon the method of analysis of his works. In addition, this paper also compares the works of Rashid Rida with those of Malay reformist writers in Malaysia